IDENTIFICATION OF CARBON FOOTPRINT IN THE CAST IN SITU PILE, CASE STUDY: GBK INDOOR MULTIFUNCTION STADIUM - Deffitania Olivia; Bambang Endro Yuwono (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2022)
The development of construction project in Indonesia is growing rapidly. In the process of building construction projects, the phenomenon of the greenhouse effectÂ has been taken part. Carbon emissions are one of the results of the greenhouse effect in the process of building construction projects. The foundation is one of the most important parts of construction that serves to hold the load and as a load distributor from the construction above the ground. In foundation work using reinforced concrete structures, reinforced concrete structures are a source of carbon emissions in construction projects. This study aims Â to find out how much carbon emissions are produced in the drilled pile work at the GBK Multifunctional Indoor Stadium project and which element produces the largest carbon emissions. The results of this study are carbon emissions produced by one bore pile with a diameter of 800 mm of 6553,78 kg.CO2 and the work of the bore pile, which produces the greatest carbon emissions, is material consumption of 6134.40 kg, CO2.